PERBANDINGAN PERFORMANSI LATENCY PROTOKOL KOMUNIKASI HTTP DAN MQTT PADA INTERNET OF THINGS - Susetyo Bagas Bhaskoro; Hadi Supriyanto; Berlian Bayu Aji; Budi Pamungkas (Jurnal Teknologi Terapan, 2022)
The objective of this study is to compare the performance (latency parameter) of HTTP and MQTT protocols. The latency parameter is the difference in time for a packet being transmitted and received. The tests are distinguished on different days and times. The results obtained are that the MQTT is better than HTTP. The results of the comparison values three times in a row are as follows: 46.6ms, 52.3ms, and 50.2ms